Geriatrician-led multidisciplinary team management improving polypharmacy among older inpatients in China - Song, Yi; Chen, Lihua; Liu, Ying; Xia, Xin; Hou, Lisha; Wu, Jinhui; Cao, Li; Mo, Li (Frontiers in Pharmacology, 2023)
Background/Aim: Polypharmacy is prevalent among older inpatients and associated with adverse outcomes. To determine whether a geriatrician-led multidisciplinary team (MDT) management mode could reduce medications use among older inpatients. Methods: A retrospective cohort study was conducted in a geriatric department of a tertiary hospital in China with 369 older inpatients, including 190 patients received MDT management (MDT cohort), and 179 patients received usual treatment (non-MDT cohort). The primary outcome was to compare the changes of the amount of medications before and after hospitalization in two cohorts. Results: We reported that MDT management significantly reduced the number of medications used in older inpatients at discharge (at home: n=7 [IQR: 4, 11] vs. at discharge: n=6 [IQR: 4, 8], P<0.05). Hospitalization with the MDT management had a significant effect on the change in the amount of medications (F=7.813, partial-η2=0.011, P=0.005). The discontinuance of medications was associated with polypharmacy at home (OR: 96.52 [95% CI: 12.53-743.48], P<0.001), and the addition of medications was associated with a diagnosis of chronic obstructive pulmonary disease (COPD) (OR: 2.36 [95% CI: 1.02-5.49], P=0.046). Conclusion: The results indicated that the geriatrician-led MDT mode during hospitalization could reduce the number of medications used by older patients. The patients with polypharmacy were more likely to “deprescription” after MDT management, while the patients with COPD were more likely to be under-prescription at home, w Polypharmacy hich could be made up for after MDT management.